About Integration Advantages of Economic and Sociological Analysis of Institutional Changes. Paper 2: Resources and Mechanisms - ШабановаМарина Андриановна (Journal of Economic Sociology, 2010)
The end (see the beginning in Т. 7. № 4). The main goal of the paper is to analyze the advantages of incorporation of the sociological approach into economic analysis of institutional changes with the help of the definitions of recourse potential of economic actors. Special attention will be given to the difficulties and problems arising here.